Jesuit History, Theatre, and Spirituality: Jonathan Moore's Inigo - Muneroni, Stefano (Religion and the arts, 2019)
The 2014 staging and publication of Jonathan Moore's play Inigo offers a unique commentary on the relationship between acting and spirituality within the Society of Jesus, the official name of the Jesuit Order. Through a close analysis of Moore's play, this article contends that Jesuit spirituality draws on performative skills to inspire exemplary behavior and foster an embodied and long-lasting response to devotional narratives. In probing post-secular readings of hagiographical drama, the author considers the reasons for the ongoing fascination exerted by saints as stage characters in contemporary plays and argues that the success of Inigo is due to its humanistic reconfiguration of the notions of sanctity, faith, and redemption, as well as to its understanding of sainthood as the result of answering a religious and artistic vocation.